2002
DOI: 10.1007/s00428-002-0613-1
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus infection in patients with liver disease: report of five autopsy cases

Abstract: Five autopsy cases of Vibrio vulnificus infection with liver disease are reported. All five patients ate raw seafood 24 h before the onset of illness. The clinical presentation was of primary septicemia, with positive cultures in both the blood and cutaneous lesions. Stool cultures were positive for the organism in one patient with gastrointestinal symptoms. Autopsy examination revealed liver cirrhosis in three cases and alcoholic liver disease in two; all showed portal hypertension. Gastrointestinal mucosal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
1
20
0
1
Order By: Relevance
“…V . vulnificus infection [9, 16, 37]. This damage has subsequently been attributed to the additive function of secreted exotoxins VvhA and MARTX [16].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…V . vulnificus infection [9, 16, 37]. This damage has subsequently been attributed to the additive function of secreted exotoxins VvhA and MARTX [16].…”
Section: Resultsmentioning
confidence: 99%
“…vulnificus intragastric (i.g.) infection, it might follow that the MARTX toxin repeat region pore, sufficient for cellular necrosis in vitro , would be sufficient for MARTX-associated intestinal damage, bacterial dissemination, and death as linked to colonization of the liver and spleen [9, 16, 37โ€“39]. Yet, the effector domain region is retained across V .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial translocation may explain how enteric bacteria become the source of infection in other organs, such as in fasciitis [11]. Chen et al [12] reported that autopsy examination of patients with V. vulnificus infection and liver dysfunction revealed portal hypertension and gastrointestinal mucosal changes. Thus, bacteria invading the fascia from the intestine by bacterial translocation, with bacterial virulence factors, may play a pathogenic role in soft-tissue infection.…”
Section: Discussionmentioning
confidence: 98%
“…A recent study from Korea is the first to report significant increases in the levels of pro-inflammatory cytokines tumor necrosis factor alpha (TNF-โฃ), interleukin-1โค (IL-1โค), and IL-6 in serum from V. vulnificus-infected patients compared to healthy individuals, confirming a role for dysregulation of the cytokine response (39). Autopsy reports from Japanese V. vulnificus cases also show a widespread inflammatory response characterized by a generalized neutrophil influx (3).…”
mentioning
confidence: 97%